2014
DOI: 10.1007/s40141-014-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of People with Lower-Limb Amputations

Abstract: Rehabilitation of persons with lower-limb amputation is a complex endeavor that requires the consideration of a multitude of factors. This article provides an overview of the current practice of prosthesis prescription, mobility training, and the utilization of wheeled mobility options in the clinical care for this population. Recent technological advancements have helped fit persons with lower-limb amputation with more functional, better fitting, and less activity-limiting artificial limbs and wheelchairs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 109 publications
0
22
0
Order By: Relevance
“…Although current prosthetic designs may adequately replace the mechanical structures of the amputated limb (Fiedler et al, 2014), there is currently no adequate, non-invasive solution for the sensory loss. In the present study, a novel approach to minimizing the sensory deficits of amputation was explored by aiming to enhance gait-and posture-relevant sensory information conferred by the prosthetic leg.…”
Section: Introductionmentioning
confidence: 99%
“…Although current prosthetic designs may adequately replace the mechanical structures of the amputated limb (Fiedler et al, 2014), there is currently no adequate, non-invasive solution for the sensory loss. In the present study, a novel approach to minimizing the sensory deficits of amputation was explored by aiming to enhance gait-and posture-relevant sensory information conferred by the prosthetic leg.…”
Section: Introductionmentioning
confidence: 99%
“…De Boer-Wilzing et al ( 2011 ) and Roffman et al ( 2014 ) showed that long prosthetic waiting times negatively affect prosthetic use and function. In fairness, these people should be offered an opportunity to recover lost strength and rebuild capacity (Fiedler et al 2014 ) after which the tool can be completed again.…”
Section: Discussionmentioning
confidence: 99%
“…4. The guiding mechanism was divided into two function phases, pulling and retracting the nylon wire in order to guide the pin until the housing: (1) In the first phase, the nylon wire is pulled up to the distal area of residual limb and it is connected to the end of the pin through a nut at the end of the wire. The pulling of the nylon wire causes the movement of the spool towards the counter clockwise direction and the roller (d) moves in the curved trough.…”
Section: Guiding Mechanismmentioning
confidence: 99%
“…Lower-limb amputation is one of the oldest known surgically performed procedures, due to trauma, vascular disease, congenital malformations and tumours [1]. People with lower limb amputation (LLA) relies on prosthetics to replace the lost limb functions, pinpoint as a crucial element in rehabilitation [2].…”
Section: Introductionmentioning
confidence: 99%